Atenção nutricional e práticas alimentares na perspectiva de gestantes com excesso de peso - Carolina da Costa Pires; Mariana Leal Rodrigues; Jane de Carlos Santana Capelli; Marta Maria Antonieta de Souza Santos; Mirian Ribeiro Baião (Universidade do Estado do Rio de Janeiro, 2020)
Objective: The aim of this study is to investigate nutritional care and dietary practices, from the perspective of overweight pregnant women receiving primary health care in the town of Macaé, Rio de Janeiro state. Methods: This is a qualitative research study, based on the interpretive paradigm. In-depth interviews were conducted, and the data underwent thematic content analysis, adapted from Bardin. Twelve overweight pregnant women, over 20 years old, living in Macaé-RJ, were interviewed. Results: The study found the establishment of vertical relationships between the health worker-patient, discontinued nutritional care and non-adherence to dietary guidelines by some participants. There was greater acceptance of excessive gestational weight gain and the adoption of ambiguous eating practices, permeated both by the excessive intake of food and by the withdrawal of foods considered to be "bad and/or junk". The vertical discourse of health workers, which is often authoritarian, and the nullification of women as an active subject in the construction of care, were implicitly reported in the narratives. Conclusion: Naturalization of gestational excess weight, conceptions built in the social imaginary such as "eating for two" and "cravings" during pregnancy, the set of eating practices in this period and family support are relevant elements to be considered by health teams for the organization of nutritional care.